3D Nanofibrous Scaffolds for Encapsulation-Controlled Vancomycin Delivery: Antibacterial Performance and Cytocompatibility - Nascimento, Tatiana Rita de Lima; Guérin, Aline Lima; Rodrigues, Mariana Souza [UNESP]; da Silva, Camila Félix; Maciel, Bruno Martins [UNESP]; Alhotan, Abdulaziz; Alhijji, Saleh; Velo, Marilia Mattar Amoêdo Campos [UNESP]; Castellano, Lúcio Roberto Cançado (MDPI, 2025)
This study aimed to engineer nanofibrous scaffolds that prioritize architecture, rather than relying solely on the drug, to achieve reproducible, long-acting local therapies. Cotton-wool-like fiber, three-dimensional (3D) poly(L-lactic acid)/polyethene glycol (PLLA/PEG) blend scaffolds were fabricated using solution blow spinning (SBS) as a customizable encapsulation platform for controlled antibiotic release. Morphological and wettability analyses were performed by scanning electron microscopy (SEM) and pendant-drop contact angle measurements, respectively. Fiber diameters were quantified using ImageJ. The chemical composition and thermal behavior were investigated by Fourier-transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA). In vitro, assays were conducted to assess the antimicrobial activity of vancomycin-loaded scaffolds against Staphylococcus aureus (disk diffusion method), as well as their cytocompatibility (Live/Dead assay in Vero cells) and hemocompatibility (ASTM F756-17 hemolysis test). All biological data were statistically analyzed using ANOVA with Tukey’s post-test, Mann–Whitney, and paired t-tests, with significance set at p ≤ 0.05. Structural optimization identified PLLA/PEG 85:15 as the most stable composition, producing homogeneous mats with high porosity and rapid wettability. Incorporation of vancomycin (10 wt.%) reduced the fiber diameter (0.23 ± 0.11 µm) compared with unloaded scaffolds (0.32 ± 0.17 µm), indicating drug–polymer interactions that modulated jet elongation. FTIR, DSC, and TGA analyses confirmed polymer miscibility and stabilization of VMC within the fibrous matrix, with no signs of degradation. Drug release exhibited a biphasic profile, with an initial burst during the first 72 h. PLLA/PEG–VMC scaffolds produced larger inhibition zones against S. aureus (18.55 mm ± 1.2 to 6.63 mm ± 0.2 at 120 h) compared with free VMC (12.91 mm ± 3.8 to 4.07 mm ± 0.6291), while blank scaffolds were inactive. Hemolysis remained within the range 2% < PLLA/PEG–VMC < 5%, indicating acceptable hemocompatibility according to ASTM standards. Although VCM-loaded PLLA/PEG scaffolds slightly reduced Vero cell viability, no statistically significant differences were observed compared with the control group. These findings demonstrate that the architecture of nanofibers presents itself as a potential platform for antimicrobial therapy with topical vancomycin in potential applications such as wound dressings or implant coatings.